The Socio-Psychological Impact of Unwanted and Abusive Calls and Messages from Unknown Numbers on Young Women: A Study of Anxiety, Stress, and Emotional Distress and Social Consequences - Ansa Tariq; Malik Kaleem Ullah; Rahmeen Fatima (Social Science Review Archives, 2025)
This research paper explores the psychological and social consequences of telephone-based harassment in young women of the University of Sargodha. The sudden and uninvited calls or messages by anonymous persons disrupt the feeling of safety of the victims and eventually destabilize their emotional balance. Empirical evidence supports the presence of a strong correlation between the prevalence of intrusive contact and high rates of anxiety, psychosocial stress and social withdrawal. The percentage of affected persons that limit communication with peers is quite substantial and thus feels more isolated and less well in general. These challenges are further advanced by the lack of institutional support and awareness at the campus communities. The current rules and policies of online safety, as well as the policies of universities, often fail to cover the actualities of such harassment. The research, therefore, highlights the urgent need of the context-relevant protection measures and the revision of the policy to ensure psychological wellbeing and the development of secure communicative conditions among the learners.